GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI ANALGESIK PADA MASYARAKAT DESA TANJUNGSARI, PETANAHAN, KABUPATEN KEBUMEN - Husnul Khuluq (Jurnal Ilmiah Kesehatan Keperawatan, 2019)
According  to WHO,  self-medication is the selection and using of drugs without a doctor's prescription by people to to treat common health issues at home . The most widely self-medicated substances are over-the-counter drugs, suplement and herbal medicine. A study in  United States and the United Kingdom found that self-medication was the main effort  to  solve health issues. This is confirmed by the results of several studies that found about 40-72%  people in several  countries practicing  self-medication. In Indonesia, according to  Basic Health Research (Riskesdas 2013) found that  103,860 (35.2%) households use self medication. Several studies have found that differences in  age, marital status,  education , occupation,  have closely related with self-medication behavior. This is the descriptive-observational study with 64 respondent The result show that many people do not understand how to practicing right self medication such as side effect drugs used in self medication, safe analgesic medication for pregnancy.Keyword : analgesic, self-medication